Multidrug Resistance, Biofilm Formation, and oprL Gene in Pseudomonas Aeruginosa from Iraqi Surgical Wounds - Abdoun Shahil, Kifah Burhan Faris (American Journal of Biology and Natural Sciences, 2026)
Background & Objective: Pseudomonas aeruginosa is a Gram negative nosocomial wound infection opportunistic pathogen highly resistant and virulent. The present study was conducted to determine the prevalence of P. aeruginosa in surgical wounds, and to investigate biofilm formation, antibiotic resistance profiles and the presence of oprL gene and their association with one another. Materials and Methods: A cross-sectional study was performed from April to October 2025 on 172 surgical wound samples in Azadi hospital and Kirkuk Teaching Hospital, Iraq. Identification was made with biochemical tests and VITEK 2. Antibiotic sensitivity was determined by Kirby-Bauer disk diffusion and colistin microdilution. Biofilm production was measured by 96-well microtiter plate and oprL gene was detected by PCR. Results: P. aeruginosa was isolated from 33.7% of samples. High resistance was observed to piperacillin (90%), ceftazidime (87%), and tobramycin (86%), while imipenem (71%) and colistin (50%) were most effective. MDR and XDR phenotypes were 55% and 26%, respectively. Biofilm analysis showed 36% strong, 31% moderate, and 33% weak/non-producers. The oprL gene was detected in 65% of tested isolates. Strong biofilm formation correlated with higher MDR/XDR rates. Conclusion: P. aeruginosa types are prevalent in surgical site infections and most isolates were MDR/XDR strains. Opportunistic Pseudomonas raw milk Isolates are likely to harbour biofilm and virulence, oprL genes which may play a role in persistence and antibiotic resistance.